Honduras : Staff Report for the 2019 Article IV Consultation and Request for a Stand-By Arrangement and an Arrangement Under the Standby Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Honduras. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2019)
This paper discusses Honduras's 2019 Article IV Consultation and Request for a Stand-By Arrangement and an Arrangement Under the Standby Credit Facility. Supported by a Fund program that expired in December 2017, Honduras has reduced macroeconomic imbalances, institutionalized fiscal prudence, and laid the groundwork for a modern monetary policy framework. The authorities are committed to maintain prudent policies and to build on previous achievements to make progress in solving long-standing issues. The authorities' economic program aims at maintaining macroeconomic stability, while enacting economic and institutional reforms to foster inclusive growth. Honduras needs to foster inclusive growth through reforms and better governance. Policy priorities include: reforms to increase the quality of fiscal policy, sustaining revenue mobilization efforts, protecting investment and social spending, and securing financial sustainability of the public electricity company; and reforms to enhance transparency and governance in the budget.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet